The Principal’s Leadership: To Create School Climate Disruption in Industrial Revolution Era 4.0 - Suherman, Irman; Mahrudin, Amir; Bisri, Hasan; Abdurrokhman, Omon; Prayitno, Agus (International Journal of Psychosocial Rehabilitation, 2020)
4.0 Industrial Era is era technology, had a negative impact on schooling, especially vocational schools if the school cannot be adapted to it. Schools should be able to create the atmosphere of the school, and at the same educational environment interaction patterns among teachers, students, staff and even the real outdoor environment (school climate) to maintain social humanistic accordance with their characteristics. But the technology is still evolving so as to adapt to the Industrial Revolution 4.0. This study aimed to determine the effect of school leadership on the climate of the school. The research was conducted in 30 vocational schools in the city of Sukabumi, while respondents who perceive about school leadership and school climate in this research were 243 teachers who have teaching experience in over 5 years. The results showed that the leadership of the principal positive effect on school climate. So if the school leadership, improved the school climate will also rise by an increase in the school leadership. Therefore, competence, motivation, and personality of principals that are characteristic of effective leadership must be constantly improved. This can be done by following education and training, Seminars, workshops, and other similar activities.